A Combined Speech-Language and Counseling Intervention for Primary Progressive Aphasia: Acceptability, Feasibility, and Preliminary Outcomes. - Mendez, Kristin Schaffer; Evans, William S.; Wauters, Lisa D.; Dutcher, Christina D.; Philburn, Christina; Henrya, Maya L. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Individuals with primary progressive aphasia (PPA) face negative psychosocial repercussions, yet few studies have investigated counseling for this population. In a prior study, a novel intervention encompassing script training and aphasia-modified cognitive behavioral therapy was piloted with an individual with PPA, yielding promising results. The purpose of this study is to determine the acceptability and feasibility of this intervention for individuals with different PPA subtypes, with secondary aims of understanding preliminary treatment outcomes and evaluating the sensitivity of selected psychosocial measures. Method: Nine participants with PPA were recruited (three with nonfluent/agrammatic variant, three with logopenic variant, and three with semantic variant). Acceptability was measured using a posttreatment questionnaire. Feasibility was examined via intervention adherence, independent practice engagement, retention, assessment completion, interrater reliability, and fidelity ratings. Speech-language outcomes were evaluated via hypothesis testing using simulation analysis from pre- to posttreatment for all participants and from pretreatment to follow-up time points for six participants. Counseling outcomes at posttreatment were measured via psychosocial scales and analyzed using Wilcoxon signed-ranks tests. Results: Findings indicate that this treatment is acceptable and feasible. All participants demonstrated significant improvement in speech-language performance following treatment, with five participants demonstrating significant improvement up to 1 year posttreatment. Despite promising qualitative evidence regarding counseling outcomes, a sensitive quantitative measure of psychosocial functioning was not identified. Conclusions: Pairing tailored speech-language interventions with counseling for individuals with heterogeneous PPA phenotypes is acceptable and feasible. Preliminary outcomes indicate positive communication findings and that alternative psychosocial measures may be beneficial in a future efficacy trial.